PELAKSANAAN KONSENSUALISME DAN IKTIKAD BAIK YANG SEIMBANG BAGI PARA PIHAK DALAM PERJANJIAN BANGUN BAGI HASIL PEMBANGUNAN RUKO MENURUT KUHPERDATA - S.H.,M.H., Yudi Hardiyanto, (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
ABSTRACT This type of research is observational reseach by means of a survey, the research that takes data directly from the population / respondents by conducting interviews and questionnaire as a data collection tool, then the data are taken from the processing performed in order to obtain a conclusion by inductive methods. From the results of research and discussion by the author that the implementation of consensual principle and good faith are balanced for both parties in agreement constructingdividing of shophouses development according to the Indonesian civil code in implementation should be properly addressed if the developer will do agreement well so that the landowner did not suffer material losses. The implementation agreement constructing-dividing for the development outcomes of this shophouses is not run in a balanced manner because the developer build first shophouses of landowners with conditions that do not conform to the agreement and then build his own shophouses so that landowners suffered material losses. Keyword: agreement constructing-dividing, concensual, good-faith, civil code